High-Expressed Macrophage Scavenger Receptor 1 Predicts Severity Clinical Outcome in Transplant Patient in Idiopathic Pulmonary Fibrosis Disease. (31st January 2021) - Zheng, Mingfeng; Tian, Tian; Liang, Jialong; Ye, Shugao; Chen, Jingyu; Ji, Yong
Abstract : Background . Lung transplantation has been performed worldwide and admitted as an effective treatment for patients with various end-stage lung diseases. However, limit reliable clinical indicators exist to identify patients at high risk for allograft failure in lung transplant recipients. The recent advances in the knowledge of immunological aspects of the pulmonary diseases, for that innate macrophage activation, are induced by pathogen or pathogen-derived molecules and widely accepted as the critical evidence among the pathogenesis of lung inflammation and fibrosis. This study was aimed at evaluating the clinical significance of CD86- and macrophage scavenger receptor 1- (MSR1-) positive cells during the development of idiopathic pulmonary fibrosis (IPF) and pulmonary arterial hypertension (PAH), and their potential roles in the prediction of the outcomes after lung transplantation were examined. Methods . Tissues from lung transplantation for 37 IPF and 15 PAH patients from the Department of Cardiothoracic Surgery in Wuxi People's Hospital from December 2015 to December 2016 were analyzed by immunohistochemistry (IHC) for detecting the expression and CD86 and MSR1 and correlated with clinical events after lung transplantation. Results . IHC results showed that the expression of MSR1, IL-13, and arginase-1 (Arg1) but not CD86 in the lung section of IPF patients was dramatically enhanced when compared with that of PAH patients. The expression of MSR1, IL-13, and Arg1 but not CD86 in the lung from IPF patients with smoking was significantly increased when compared with that from nonsmoking subjects. In addition, the expression of MSR1-positive cells in IPF subjects with Klebsiella pneumoniae infection was dramatically enhanced than that in noninfection subjects. MSR1-positive macrophages were negatively associated with FEV1 and with FVC but not associated with TLC and with TLCO . However, CD86-positive macrophages were not significantly associated with the above lung function-related factors. Furthermore, MSR1 had a higher area under the ROC curve (AUC) than CD86 for IPF diagnosis. Survival analysis indicated that high levels of MSR1-positive macrophages had a worse prognostic effect for IPF patients with lung transplantation. Conclusion . Our study indicates the clinical significance of Klebsiella pneumoniae infection-related MSR1-positive cells in IPF progression, and it could be a prognostic marker in IPF after the lung transplant; development strategies to reduce the expression of MSR1-positive macrophages in IPF may be beneficial for the lung transplant.